With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Performing the body: performing the text - Jones, Amelia..; Stephenson, Andrew; Jones, Amelia; Stephenson, Andrew (Routledge, 1999)
This book explores the new performativity in art theory and practice, examining ways of rethinking interpretive processes in visual culture. Since the 1960s, visual art practices - from body art to minimalism - have taken contemporary art outside the museum and gallery; by embracing theatricality and performance and exploding the boundaries set by traditional art criticism. The contributors argue that interpretation needs to be recognised as much more dynamic and contingent. Offering its own performance script, and embracing both canonical fine artists such as Manet, De Kooning and Jasper Johns, and performance artists such as Vito Acconci and Gunter Brus, this book offers radical re-readings of art works and points confidently towards new models for understanding art.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; premier cycle; périodes historiques; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Femmes au miroir: une histoire de l'autoportrait féminin - Borzello, Frances (Thames & Hudson, 1998)
Une sélection d'autoportraits féminins empruntés à toute l'histoire de l'art, de la religieuse anonyme qui glissa son effigie dans la lettrine d'un manuscrit du XIIe siècle à Cindy Sherman et ses photogrammes révélateurs des visions stéréotypées de la femme, en passant par Sofonisba Anguissola, Artemisia Gentileschi, Elisabeth Vigée-Lebrun, Frida Kahlo, Hannah Wilke, etc.
Section: 224 pages : illustrations ; 29 cm
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Disponible en ligne: https://link-springer-com.proxy.bibliotheques.uqam.ca/article/10.1057/fr.1997.7
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

An intimate distance: women, artists and the body - Betterton, Rosemary.. (Routledge, 1996)
How have women artists taken possession of the female body? What is the relationship between looking and embodiment in art made by women? In a series of original readings of the work of artists from Kathe Kollwitz and Georgia O'Keeffe to Helen Chadwick and Laura Godfrey-Isaacs, Rosemary Betterton explores how women artists have addressed the changing relationship between women, the body and its representation in art. In detailed critical essays that range from the analysis of maternal imagery in the work of German artists at the turn of the century to the unrepresented body in contemporary abstract painting, Betterton argues that women's art practices offer new ways of engaging with our fascinations with and fears about the female body. Reflecting the shift within feminist art over the last decade, An Intimate Distance sets the reinscription of the body within women's art practice in the context of current debates on the body, including reproductive science, maternal subjectivity and the concept of 'body horror' in relation to food, ageing and sex. Drawing on recent theories of embodiment developed within feminist philosophy and psychoanalytic theory, the essays reveal how the permeable boundaries between nature and culture, the female body and technology are being crossed in the work of women artists.
Keywords: 1900-1999; approches et analyses; art contemporain; artistes féministes; arts; corps; cours; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

The art of reflection: women artists'self-portraiture in the twentieth century - Meskimmon, Marsha.. (Columbia University Press, 1996)
Self-portraiture has long been a means for the male artist to assert an identity as masterful creator or tortured soul; women have overwhelmingly been presented as objects, and rarely as subjects of self-portraiture. In recent years, however, women artists have used their work to disrupt this tradition. With 43 illustrations of works by Louise Bourgeois, Frida Kahlo, Alice Neel, Cindy Sherman, and Jo Spence, among others, The Art of Reflection is the first sustained inquiry into the appropriation of self-portraiture by women. In suggestive critical meditations on paintings, photographic work, sculpture, performance art, and body art, Marsha Meskimmon shows how twentieth-century women artists have undermined male-centered definitions of how "the artist" depicts the self. Drawing upon feminist theory and philosophy from Simone de Beauvoir to Luce Irigaray, The Art of Reflection casts doubt on the idea of self-portrait as a mirror, in which the static self is rendered accurately and naturalistically. Meskimmon evokes a series of myths about what an artist is, how "he" should be represented, and how "his" work is to be read as autobiography. Through close readings of the imaginative self-representations of women artists -as male artist and god, as central player in the studio and in the Christian passion- she shatters these myths. In an absorbing assessment of the ways women artists have negotiated the complex group of roles ascribed to "woman," Meskimmon considers the partially nude painting by pregnant artist Paula Modersohn-Becker and performance artist Annie Sprinkle's confrontation of the thin line between celebration of female sexuality and objectification of the female body. As a nuanced appreciation of the interpretations of self-portraiture among women artists, The Art of Reflection will prove an invaluable resource on a subject that has received little attention from art criticism. Meskimmon's work also presents a bold challenge to critical tradition, compelling readers to rethink the meaning of the genre as a whole.
Keywords: 1900-1999; arts; corps; cours; critique d'art; discipline; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; représentation; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Féminisme, art et histoire de l'art - Tucker, Marcia; École nationale supérieure des beaux-arts (France) (École nationale supérieure des Beaux-Arts, 1994)
Ces cinq contributions d'historiennes de l'art et de femmes agissant dans le monde de l'art posent la question des apports du féminisme à l'art récent et au renouvellement de l'histoire de l'art, discipline largement régie, jusqu'au début des années 70, par le regard des hommes. Le féminisme a contribué à renouveler notre conception de l'art. Les auteurs de ce recueil comptent parmi les figures majeures de ce débat.
Cet ouvrage fait suite au colloque Féminisme, art et histoire de l'art, çà, c'est une autre histoire, tenu de janvier à mars 1990 à l'École nationale supérieure des beaux-arts.
Keywords: 1900-1999; 1970-1979; 1980-1989; art occidental; arts; cours; discipline; har4600; har4610; histoire de l'art; premier cycle; périodes historiques

Femmes, art et pouvoir et autres essais - Nochlin, Linda (Jacqueline Chambon, 1993)
Plusieurs essais, rédigés à partir de 1969, qui abordent les sujets des représentations féminines dans l'art, entre la fin du XVIIIe siècle et le XXe siècle, l'érotisme et les images du féminin dans l'art du XIXe siècle et la question pourquoi n'y a-t-il pas eu de grands artistes femmes. L'auteur identifie l'idéologie dominante sur laquelle repose la place donnée aux femmes.
Première publication: 1991 Titre original: Women, Art, and Power, and Other Essays.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; domination masculine; fem1000; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; rapports de domination; rapports sociaux de sexe; systèmes d'oppressions; thématiques; théories féministes

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Première publication : 1991
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Interrogating identity - Phillips, Meredith L.; Grey Art Gallery & Study Center (Grey Art Gallery and Study Center, New York University, 1991)
Exposition collective regroupant : Araeen, Rasheed, 1935- ; Belmore, Rebecca, 1960- ; Chan, Nadine ; Chong, Albert ; DeSouza, Allan, 1958- ; Hassan, Jamelie, 1948- ; Hatoum, Mona, 1952- ; Kempadoo, Roshini ; Ligon, Glenn, 1960- ; Lovell, Whitfield, 1959- ; Maestro, Lani, 1957- ; Mulero, Lillian, 1950- ; Mur-Ray, Ming ; Piper, Keith, 1960- ; Pollard, Ingrid, 1953- ; Rodney, Donald, 1961-1998 ; Shonibare, Yinka, 1962- ; Simmons, Gary.
Section: 143 pages : illustrations (certaines en couleur) ; 23 x 31 cm
Keywords: arts; cours; discipline; har4610; histoire de l'art; identités culturelles; premier cycle

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

The Decade show: frameworks of identity in the 1980s - Young, Louis; New Museum of Contemporary Art (New York, N.Y.); Studio Museum in Harlem; Museum of Contemporary Hispanic Art (New York, N.Y.) (Museum of Contemporary Hispanic Art, 1990)
The Decade Show is a provocative examination of artistic production in the 1980s, embracing 113 artists and artists’ groups (including Ida Applebroog, Luis Cruz Azaceta, Gran Fury, Edgar Heap-Of-Birds, Komar & Melamid, Adrian Piper and Shu Lea Cheang) who - whether visible or invisible in the mainstream - are critical to an understanding of the period. Fourteen essayists, among them David Deitcher, Thelma Golden, Julia P. Herzberg, Micki McGee, Sharon F. Patton, Susan Quist and Lowery Stokes Sims, contribute to this extensive survey. As a collaborative effort between the Museum of Contemporary Hispanic Art, The New Museum and The Studio Museum in Harlem, The Decade Show reflects true community diversity, as well as the museum’s interest in examining “parallel cultures” obscured by traditional aesthetics. “This is not a patronizing exhibit of the art of ‘exotica’ put together by the philanthoropic goodwill and high-art-world curiosity of a few white curators. It is an exhibit attempting to construct a multivocal art world. It begins to suggest that the notion of a ‘center’ and a ‘margin’ is anachronistic and that maintaining such a model represents a desire to wield exclusive power and control.” -Eunice Lipton, “Here Today, Gone Tomorrow,” p. 20.
Section: 364 pages : illustrations (certaines en couleur)
Keywords: amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; intersectionnalité; point de vue situé; premier cycle; queer; régions géographiques; états-unis